Roots and Returns: An Afropolitan Reading of Food in Francesca Ekwuyasi’s Butter Honey Pig Bread - Strong, Sara-Ann (Cuizine, 2025)
Food, food related imagery, and food vocabulary are integral to Francesca Ekwuyasi’s acclaimed debut novel Butter Honey Pig Bread (2020). Beyond the edible items enumerated in the title, the narrative features numerous scenes of meals, kitchen prep, restaurants, culinary schools, and feasts, not to mention recurring imagery associated with the tastes and smells of food. This essay begins with Afropolitan conceptions of movement and class throughout the African diaspora to illuminate the way that food relates to plot, characterization, theme, and symbolism in Butter Honey Pig Bread. After establishing the premise that food is distinctly multidirectional in Ekwuyasi’s novel, this essay suggests that food operates to complexify the protagonists’ experiences of time and space by blurring the lines between youth and adulthood and between Canada and Nigeria. The main points of this essay offer an exploration of food’s ability to address the tension between the characters in their home through the sites dedicated to food such as the kitchen and the garden. Food divisions in the novel also gesture to the inherent privilege of the Afropolitan and the tensions within Afropolitanism. Food embodies these tensions as much as they defy them, temporally and spatially. In Butter Honey Pig Bread, sites of painful memories such as gardens and slaughterhouses are awaiting the creation of a memory that acts as a balm to the wound the pain creates. Ultimately, food in Butter Honey Pig Bread is a vehicle that simultaneously displaces and returns its passengers—the protagonists—home, wherever and whenever that may be.